Processing Beyond Drawing: A Case Study Exploring Ideation for Teaching Design - Orthel, Bryan D.; Day, Julia K. (My University, 2017)
Designers’ internal thought processes can be externally expressed and represented through sketching and other forms of communication. Novice designers often struggle to communicate their ideas. This article reports an analysis of student design processes during conceptual and schematic design development with the intention to inform teaching and learning activities. Interior design student teams provided sketches, written journal entries, digital drawings and models, and graphic images to illustrate their collective design processes. The work was analyzed to understand the students’ representation and development of ideas. Analysis revealed that sketching, digital media, and non-graphic process work were all valuable in the students’ design process. Significantly, the strength of the design outcomes aligned more with the overall quality of conceptual process work, rather than the way in which students represented their ideas. Ultimately, student understanding of the design process varied. Teaching and learning activities should develop direct connections with design thinking processes to improve design education. © 2016, © The Author(s) 2016.
Citation: Orthel, B. D., & Day, J. K. (2016). Processing Beyond Drawing: A Case Study Exploring Ideation for Teaching Design. SAGE Open, 6(3). doi:10.1177/2158244016663285
Keywords: Communication; Design Process; Drawing; Teaching And Learning